PRODUCTIVITY AND COST ANALYSIS OF DRILLING FOR BLAST HOLES IN GRANITE MINING AT PT. HANSINDO MINERAL PERSADA - Prayitno, Dwi Angga; Syahrudin, Syahrudin; Syafrianto, M. Khalid (Fakultas Teknik Universitas Tanjungpura, 2024)
Granite's durability makes it a popular choice in construction, but efficient granite mining, especially through drilling for blast holes, is essential for productivity and cost management. PT. Hansindo Mineral Persada in Kalimantan Barat faces challenges balancing drilling efficiency and costs, requiring a detailed study to optimize operations. This article presents a study analyzing drilling machine productivity, focusing on the rotary-percussive method based on 2022 drilling costs. The study revealed insights into drilling productivity, obstacles, and costs. Notably, productivity, measured by Net Penetration Rate (NPR) and Gross Penetration Rate (GPR), showed significant improvements: NPR for machine 001 increased from 71.39 m ³/hour to 95.24 m ³/hour, and GPR from 58.02 m ³/hour to 75.35 m ³/hour. Machine 002